International large-scale assessments in education : insider research perspectives - Maddox, Bryan (Bloomsbury Academic, 2018)
International Large-Scale Assessments in Education explores the often controversial, international large-scale educational assessments (ILSAs) and offers research-based accounts of international testing practices as social practice. Assessment exercises, such as the Organisation for Economic Co-operation and Development's Programme for International Student Assessment (PISA), produce comparable international statistics and rankings on educational performance, and are hugely influential practices that shape educational policy on a global scale. Chapters in this volume, written by expert researchers in the field, take the reader behind the scenes to document a broad range of ILSA practices - from the recruitment of countries into international assessments, to the production and performance of large-scale testing, and the management, media reception and use of test data. Based on data normally only available to expert researchers with access inside international assessment organisations, the international case study material includes examples of ILSAs from Australia, Ecuador, Germany, Japan, Mexico, Norway, Russia, Scotland, Slovenia, Sweden, the UK and the USA. The volume provides important insights for teachers, researchers and policy-makers who use and study assessment data and who wish to evaluate its significance for educational policy and practice.